Answer:
d=-4 and a=10
Step-by-step explanation:
The sum of a arithmetic sequence is given by (n/2)*(2a+(n-1)d). Comparing coefficients with the given Sn, we have; a-d/2=12 and d/2=-2, d=-4 and a=10.
Answer:
y = -3x - .25 or y = -3x + -.25
Step-by-step explanation:
y = slope (x) + y-intercept
-4 = -3(1.25)+b
-4 = -3 .75 + -.25
-4 = -4
Answer:
y = -2x - 6
Step-by-step explanation:
Find the gradient: y difference/x difference
0 - (-6) / -3 - 0
6 / -3
= -2
y = mx + c
-6 = -2 × 0 + c
-6 = c
= C = -6
B is false but C and D are true
Answer:
step 2 is where she made her mistake
Step-by-step explanation:
- 4x + 1 > 9 ( subtract 1 from both sides )
- 4x > 8
divide both sides by - 4 , reversing the symbol as a result of dividing by a negative quantity.
x < - 2